2017
DOI: 10.3174/ajnr.a5141
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Brain Lesions during Acute Optic Neuritis and/or Longitudinally Extensive Transverse Myelitis May Portend a Higher Relapse Rate in Neuromyelitis Optica Spectrum Disorders

Abstract: Background and purpose Neuromyelitis optica spectrum disorders (NMOSD) is an inflammatory demyelinating disorder with optic neuritis (ON) and/or longitudinally extensive transverse myelitis (LETM) episodes. We now know that NMOSD is associated with antibodies to aquaporin 4 (AQP4) which is highly concentrated on astrocytic end-feet at the blood-brain barrier. Immune-mediated disruption of blood brain barrier may manifest as contrast enhancement (CE) on brain MRI. We aim to delineate extent and frequency of CE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Patterns of Enhancement.-Enhancement on T1-weighted images is detected in 9%-36% of NMOSD patients (38). Enhanced brain lesions in NMOSD have been associated with higher relapse rates when these MR imaging features are depicted at follow-up within 1 month of diagnosis of acute optic neuritis or LETM (59). The most common pattern of gadolinium enhancement is cloud-like, which is characterized as patchy and inhomogeneous with poorly defined margins ( Fig 8a) (38,51,55,60).…”
Section: Mr Imagingmentioning
confidence: 99%
“…Patterns of Enhancement.-Enhancement on T1-weighted images is detected in 9%-36% of NMOSD patients (38). Enhanced brain lesions in NMOSD have been associated with higher relapse rates when these MR imaging features are depicted at follow-up within 1 month of diagnosis of acute optic neuritis or LETM (59). The most common pattern of gadolinium enhancement is cloud-like, which is characterized as patchy and inhomogeneous with poorly defined margins ( Fig 8a) (38,51,55,60).…”
Section: Mr Imagingmentioning
confidence: 99%
“…Expansion and T1 hypointensity are common features in the acute attack of demyelinating/inflammatory entities as contrast enhancement. 23,24 Different patterns of contrast enhancement have been identified in NMOSD, such as cloudlike parenchymal, pencil-thin ependymal, leptomeningeal, or perivascular enhancement. [24][25][26][27][28] Among these, ependymal and leptomeningeal enhancement was found significantly more frequently in patients with NMOSD than in those with MS and was suggested as a characteristic feature in NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Different patterns of contrast enhancement have been identified in NMOSD, such as cloudlike parenchymal, pencil-thin ependymal, leptomeningeal, or perivascular enhancement. [24][25][26][27][28] Among these, ependymal and leptomeningeal enhancement was found significantly more frequently in patients with NMOSD than in those with MS and was suggested as a characteristic feature in NMOSD. 27 In our study, we found similar results regarding leptomeningeal enhancement; it was seen in 3 patients (37.5%) with NMOSD and was not detected in patients with ADEM (P ϭ .23).…”
Section: Discussionmentioning
confidence: 99%
“…Atypical ON can be part of the neuromyelitis optica spectrum (NMO), 27 corticosteroid-dependent chronic relapsing inflammatory optic neuropathy (CRION), and systemic diseases such as sarcoidosis, connective tissue diseases (systemic lupus erythematosus, Sjögren's syndrome, and polyarteritis nodosa), and vasculitis (Wegener's granulomatosis). 25,28,29 Others are infectious causes such as Lyme disease, neurosyphilis, tuberculosis, HIV, cytomegalovirus, varicella zoster, toxoplasmosis, and cryptococcosis, among others.…”
Section: Medical Imaging Findingsmentioning
confidence: 99%